Tecnologia blockchain na mitigação de vulnerabilidades à corrupção - Souza, Rodrigo Couto de (2020)
Corruption is the cause of a large portion of the social problems that degrade society, despite the innumerable initiatives to reduce this practice, there are still many recorded occurrences and in this scenario, the effort to fight corruption is constantly growing. Corruption in the area of public administration is related to a lack of control, especially in governments where internal rules and controls are unclear, where the accountability or inspection system is small or non-existent and where information is not transparent. This research investigates the fight against corruption with the use of blockchain technology as an alternative to mitigate vulnerabilities to corruption. The research question to be answered is: What characteristics of the blockchain can mitigate vulnerabilities to corruption? Based on the research question and the theoretical framework, the bibliographic research method was chosen, which is built from the search for references of works analyzed and published in recognized media. As a technique of data collection, interviews were carried out with specialists, in addition to the analysis of documents related to the theme. The results allowed the identification of vulnerabilities to corruption and characteristics of the blockchain, which were related according to the greater adherence of mitigation to corruption, enabling the systemic understanding of their relationships. The recognition of these relationships provides greater assertiveness regarding the adoption of blockchain technology in combating vulnerabilities to corruption.